History of Rabies Incidence and Rabies Control in Serbia in Support of the Zero by 2030 Campaign to Eliminate Dog-Mediated Human Rabies - Srđan Stankov; Dušan Lalošević; Anthony R. Fooks (Viruses, 2021)
Urban (principally canine-mediated) rabies has been a public health risk for people living in Serbia for centuries. The first legal act in urban rabies prevention in Serbia was established in 1834 by introducing high taxes for pet dog owners. Five years later in 1839, the first set of literature describing rabies prevention was issued by the health department from The Serbian Ministry of Interior. An overview of cauterization of rabies wounds was presented as the principal method of rabies post exposure prophylaxis. In 1890, a human rabies vaccination was introduced in Serbia with the royal government directive which ordered patients to be treated at the Pasteur Institute in Budapest in receipt of rabies vaccination. Urban (canine) rabies was eliminated during the 1980s, but sylvatic (principally fox-mediated) rabies still prevailed. The last human rabies case was recorded in the Province of Kosovo and Metohija in 1980. Sylvatic rabies in Serbia is in the final stages of elimination by orally vaccinating foxes (Vulpes vulpes). The only published finding of a lyssavirus among Serbian bats was made in 1954 by Dr Milan Nikolić in the vicinity of Novi Sad. In 2006, a comprehensive two-year active surveillance program of lyssaviruses in bats in Serbia was undertaken. In this single study, all of the bats from Serbia tested negative for a lyssavirus.